Have We Passed Peak Capitalism? - Blair Fix (Real-World Economics Review, 2022)
This paper uses word frequency to track the rise and potential peak of capitalist ideology. Using a sample of mainstream economics textbooks as my corpus of capitalist thinking, I isolate the jargon of these books and then track its frequency over time in the Google English corpus. I also measure the popularity of feudal ideology by applying the same method to a sample of Christian bibles. I find that over the last four centuries, biblical language fell out of favor and was replaced by the language of economics. Surprisingly, however, I find that since the 1980s, the trend has reversed. Today, the language of economics is waning, while biblical language is on the rise. Is this evidence that we've passed the peak of capitalist ideology?
Keywords: P16; 330; capitalism; economics; ideology; language; religion